Religious Moderation is Viewed Through Emotional Intelligence: A Study among University Students - Paska, Paskalis Edwin I Nyoman; Kusumawanta, Dominikus I Gusti Bagus (Kuras Institute, 2025)
Indonesia's plurality is a priceless gift. Unfortunately, in terms of religion, conflict has colored the history of this nation. This study aims to analyze the effect of Emotional Intelligence on Religious Moderation among students in Sekolah Tinggi Pastoral (STP) – IPI Malang. With probability sampling technique, 175 samples were obtained. This research uses a quantitative approach, and data collection using a questionnaire. The research findings show, the correlation coefficient between the criterion variable and the predictor is proven to be very strong (r = 0.980), and the coefficient of determination of 0.960 shows that the predictor variables simultaneously affect the criterion variable (Religious Moderation) by 96%, the rest (4%) is influenced by other variables outside this study. In terms of causality, the predictor variables simultaneously affect the Religious Moderation variable, with a value of F = 0.000 < α (α = 0.05). While, partially the variables of perceiving emotions, using emotions to facilitate thought, understanding emotions, and managing emotions are also proven to have a significant effect on Religious Moderation (t-statistics value of perceiving emotions by 19.230 > 1.96; using emotions to facilitate thought by 3.526 > 1.96; understanding emotions by 6.163 > 1.96; and managing emotions by 2.126 > 1.96). The variable perceiving emotions contributes the most, and the variable managing emotions contributes the least. It can be concluded, both simultaneously and partially, all predictor variables have a significant effect on Religious Moderation.